An efficient decoding algorithm for block turbo codes. - Dave, S. (IEEE Transactions on communications)
An efficient soft-input soft-output iterative decoding algorithm for block turbo codes (BTCs) is proposed. The proposed algorithm utilizes Kaneko's (1994) decoding algorithm for soft-input hard-output decoding. These hard outputs are converted to soft-decisions using reliability calculations. Three different schemes for reliability calculations incorporating different levels of approximation are suggested. The algorithm proposed here presents a major advantage over existing decoding algorithms for BTCs by providing ample flexibility in terms of performance-complexity tradeoff. This makes the algorithm well suited for wireless multimedia applications. The algorithm can be used for optimal as well as suboptimal decoding. The suboptimal versions of the algorithm can be developed by changing a single parameter (the number of error patterns to be generated). For any performance, the computational complexity of the proposed algorithm is less than the computational complexity of similar existing algorithms. Simulation results for the decoding algorithm for different two-dimensional BTCs over an additive white Gaussian noise channel are shown. A performance comparison of the proposed algorithm with similar existing algorithms is also presented